2019
DOI: 10.1080/14756366.2019.1677637
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, activity and mechanism of alkoxy-, carbamato-, sulfonamido-, thioureido-, and ureido-derivatives of 2,4,5-trimethylpyridin-3-ol against inflammatory bowel disease

Abstract: 2020) Synthesis, activity and mechanism of alkoxy-, carbamato-, sulfonamido-, thioureido-, and ureido-derivatives of 2,4,5-trimethylpyridin-3-ol against inflammatory bowel disease, ABSTRACT Inflammatory bowel disease (IBD) is a chronic immuno-inflammation in gastrointestinal tract. We have evaluated the activity of the compounds to inhibit the adhesion of monocytes to colon epithelial cells is triggered by a pro-inflammatory cytokine, tumour necrosis factor (TNF)-a. The in vitro activity of the compounds, 13b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
7
0
5
Order By: Relevance
“…of p-toluidine (2 a) in DMF at 120 °C showed almost good yield (77%) of the desired product 3 a for 20 h (Table 1, entry 1). The formation of the target product -1-(4-methylpyridin-2yl)-3-(p-tolyl)urea (3 a) -was confirmed by 1 H and 13 C NMR spectroscopy, HRMS as well as X-ray diffraction analysis of the product crystals (Figure 2). Encouraged by the first success, we tried to change the N,N'-dialkyl substituent in starting urea from piperidine moiety to the dimethylamino group (Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…of p-toluidine (2 a) in DMF at 120 °C showed almost good yield (77%) of the desired product 3 a for 20 h (Table 1, entry 1). The formation of the target product -1-(4-methylpyridin-2yl)-3-(p-tolyl)urea (3 a) -was confirmed by 1 H and 13 C NMR spectroscopy, HRMS as well as X-ray diffraction analysis of the product crystals (Figure 2). Encouraged by the first success, we tried to change the N,N'-dialkyl substituent in starting urea from piperidine moiety to the dimethylamino group (Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 91%
“…N-Heteroaromatic substituted ureas are extensively used compounds for drug design (Figure 1). [1,2] There are numerous examples of their manifestation as therapeutics for treatment of neurodegenerative diseases (especially Alzheimer's disease [3][4][5][6] ), diabetes, [7][8][9][10][11] cardiovascular disorders, [12] and also as anti-inflammatory agents [13] and antibiotics. [14][15][16][17] Moreover, there is a growing body of research shows that substances bearing N-pyridylurea moiety have antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported 6-alkylamido-2,4,5-trimethylpyridin-3-ols as dual inhibitors against both TNFα- and IL-6-induced inflammatory activity in in vitro IBD models, employing a phenotype-based drug discovery strategy. , Analogues with phenylethyl ( 6 – 29 ), benzyl, and cyclohexyl side chains attached to the 6-amido functional group showed high activity, possibly owing to some degree of flatness provided by these side chains. In this study, for better dual inhibition, we expanded the scope of the side chains to increase their flatness and attached them directly to the amido functional group.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that Bifidobacterium infantis ( B. infantis ) can alleviate intestinal epithelial injury and maintain intestinal immune tolerance in a mouse model of IBD and may have therapeutic implications for the immunological injuries observed in IBD . Bifidobacterium infantis notably increased the expression levels of PD-L1 and PD-1 in the intestine and promoted the expression of nuclear transcription factors and of anti-inflammatory factors (IL-10 and TGF-β1) in Tregs[ 22 , 23 ]. Therefore, this study aimed to explore the mechanism of action of B. infantis in the PD-1/PD-L1 signaling pathway and the differentiation and function of Tregs.…”
Section: Introductionmentioning
confidence: 99%